Metal doped nanocomposites for detection of pesticides and phenolic compounds by colorimetry: Trends and challenges - Sammi Boher; Rooh Ullah; Mustafa Tuzen; Tawfik A. Saleh (Elsevier, 2023)
Colorimetric methods are classical techniques that have been broadly subjected to and applied for the detection of many analytes. The method is low cost, simple, practically active, and suitable to determine the sample due to color changes which are accessed visually even at low concentrations of target analysis. Hence, different methods are applied for detecting and determining pesticides (insecticides) and phenolic compounds (bisphenol A). Moreover, researchers detected OCPs (Organochloride pesticides) in breast milk and adipose tissues, which may exhibit estrogenic, and antiestrogenic activities mostly associated with breast cancer. The common thing between two the analytes is nature because they both show endocrine-disrupting properties. Bisphenol A (phenolic compound) is commonly used in the high-volume production of monomers and plastics. Bisphenol A is used to manufacture polycarbonate plastics, used in food cans coating, baby formula bottles, milk containers, paints, etc. Pesticides and phenolic compounds identification methods can be sluggish and need extremely skilled workforces to function cultured instruments that are mostly too expensive, delicate, or immense to a position outside of a devoted laboratory facility. This review deals with the discriminatory and low-cost method for the colorimetric detection of pesticides and phenolic compounds (bisphenol A) with different bio-synthesized metals and metal-doped nanocomposites. Based on existing publications, using colorimetry with nanocomposites provides low detection limits and good reproducibility for the detection of pesticides and phenolic compounds in various samples such as food samples. These results serve as a guide for controlling pesticides and phenolic chemicals in food processing, lowering the dangers involved.